Nearly coeval intermediate-age Milky Way star clusters at very different dynamics evolutionary stages - Piatti, Andres Eduardo (2019)
We report astrophysical properties of 12 Milky Way open clusters located beyond a 2 kpc circle around the Sun by using deep optical photometry. We estimated their age and metallicities on the basis of a maximum likelihood approach using astrometric members determined from Gaia DR2 data. The studied clusters turned out to be of intermediate-age (0.8-4.0 Gyr), with metallicities spanning the range [Fe/H] ∼ −0.5-+0.1 dex, and distributed within the general observed trend of the Milky Way disc radial and perpendicular metallicity gradients. As far as we are aware, these are the first metal abundance estimates derived for these clusters so far. From the constructed stellar density radial profiles and cluster mass functions we obtained a variety of structural and internal dynamics evolution parameters. They show that while the innermost cluster regions would seem to be mainly shaped according to the respective internal dynamics evolutionary stages, the outermost ones would seem to be slightly more sensitive to the Milky Way tidal field. The nearly coeval studied clusters are experiencing different levels of two-body relaxation following star evaporation; those at more advanced stages being more compact objects. Likewise, we found that the more important the Milky way tides, the larger the Jacobi volume occupied by the clusters, irrespective of their actual sizes and internal dynamics evolutionary stages.